Multiple Quasisynchronization of Uncertain Fractional-Order Delayed Neural Networks by Impulsive Control Mechanism - Biwen Li; Lin Xu (Complexity)
We study the dynamical behavior of multiple quasi-synchronization of a type of fractional-order coupled neural networks (FCNNs) with delay and uncertain parameters. By utilizing the pinned pulse control strategy technique, we establish a new pulse controller, which realizes the multiple quasisynchronization of the system. Furthermore, we derive some new criteria of multiple quasisynchronization by using the comparison principle and mathematical analysis. Eventually, simulations are carried out with two examples to explicate the effectiveness of the conclusions.